IN THE PROCESS OF INITIAL PREPARATION MODERN STRUCTURE OF THE TRAINING PROCESS IMAGINATIONS - Sh. N. Nuritdinova (Innovate Conferences, 2025)
Sport is one of the main means of forming a mentally and physically healthy generation.Taekwondo is one of the actively developing sports in our country. One of the urgent problems of young taekwondo players is finding ways to improve their sports skills.